Preparation and Characterization of Polyvinyl Acetate (Kollidon® SR) Microspheres Containing Diclofenac Sodium II: Effect of core loading (Dhaka University Journal of Pharmaceutical Sciences, 2010)
Diclofenac Sodium (DS) loaded Kollidon® SR (Polyvinyl acetate and povidone based matrix retarding polymer) microspheres of different drug loading were prepared using W/O emulsification solvent evaporation technique. Polymeric solution containing the DS was emulsified in light liquid paraffin (LLP) which was initially emulsified by 1% (w/w of the continuum) lipophilic surfactant Span 60. The study was conducted to investigate the effect of different core to polymer ratio (0.5: 1, 1 : 1, 1.5 : 1 and 2 : 1) on microsphere size, encapsulation efficiency and release kinetics of DS. Microsphere size was decreased with increased core loading. However, higher encapsulation efficiency was observed with higher core loading. A square root of time dependent release of DS was observed from the KSR microspheres. Increased core loading caused faster release of DS. Release rates of DS were affected by different DS content in the core. Normalized release rates were also found to be increased with high core loading. Mean dissolution time (MDT) and t50 values were also calculated and were found to be affected significantly by different DS loading to KSR microspheres. Low DS loading increased MDT. Key words: Kollidon® SR; Diclofenac Sodium; Microsphere; Solvent evaporation technique; Mean dissolution time. DOI: 10.3329/dujps.v8i2.6025 Dhaka Univ. J. Pharm. Sci. 8(2): 117-122, 2009 (December)